All dogs go to heaven [videorecording (DVD)] - Bluth, Don; Anderson, Loni, 1945-; Barsi, Judith, 1978-1988; DeLuise, Dom; Moore, Melba; Reilly, Charles Nelson; Reynolds, Burt (MGM Home Entertainment, 2003)
Out for revenge against his double-crossing former partner, the roguish German Shepherd Charlie, finds himself guardian to a lonely little orphan named Anne-Marie. Her astounding ability to talk to animals leads this unlikely pair on an adventure packed with thrills, laughter, tears, and true love.